Emotional Readiness Towards Marriage Analysis of Household Financial Management Reviewed According to Islamic Family Law : Case Study on Youth of Ideal Marriage Age in Indragiri Hilir Regency - Meiretno, Dwiky; Basri, Helmi; Suhayib, Suhayib (Tasyri' : Jurnal Muamalah dan Ekonomi Syariah, 2024)
This research discusses the Emotional Readiness Towards Marriage Analysis of Household Financial Management Reviewed According to Islamic Family Law Case Studies on Youth of Ideal Marriage Age in Indragiri Hilir Regency. The problem in this study is the high number of unmarried youth in Indragiri Hilir Regency based on data obtained from the Central Bureau of Statistics and the increasing number of unmarried youth in the last 3 (three) years. It also discusses the emotional readiness efforts of young people of ideal marriage age in Indragiri Hilir district with the analysis of Household Financial management, and the review of Islamic Family Law. The purpose of this research is the effort of emotional readiness in young people of ideal marriage age with the analysis of household financial management, and the review of Islamic Family Law. The research method used is field research, which starts from data collection: questionnaires / questionnaires, observation, interviews, and documentation. The data will be traced in the relevant literature. The results showed that emotionally the picture is positive about the readiness of the younger generation in facing married life. youth aged 19-26 years, the majority showed good emotional readiness, feeling emotionally ready to face challenges in marriage and able to manage emotions in conflict situations. In terms of financial management, the youth consider financial management as an important factor, with most having prepared a budget plan and believing that saving and investing are important steps to achieve family financial stability. In terms of Islamic family law views, respondents accepted the concept of nafkah as an obligation of the husband to the wife and felt it was important to manage household finances in accordance with Islamic principles, and showed readiness to discuss property rights and management in accordance with Islamic law.